The Impact of Social Networking Sites With Its Positive and Negative Aspects - Sharma, Pooja; Malhotra, Vaishali; Kour, Randeep (International Journal of Computer Sciences and Engineering, 2025)
Social networking sites provides productive medium to build relations with others and share information related to jobs, upcoming carrier opportunities and their life experiences also. In Today’s time the social sites preferred stomping ground in cyberspace. Every Technology has its good and adverse effects on society likewise social sites has many fors and againsts.The social networking sites like https://instagram.com/,https://linkedin.com/https://facebook.com/ etc are incessantly disturbing students from their studies. Social networks are only electronic association between users but unluckily it has become an addiction for students, teenagers and even adults. This paper contains both merits and demerits of social media and their impact.